Coral‐Derived Western Pacific Tropical Sea Surface Temperatures During the Last Millennium - Tianran Chen; Kim M. Cobb; George Roff; Jianxin Zhao; Hongqiang Yang; Minhang Hu; Kuan Zhao (Geophysical Research Letters)
Abstract Reconstructions of ocean temperatures prior to the industrial era serve to constrain natural climate variability on decadal to centennial timescales, yet relatively few such observations are available from the west Pacific Warm Pool. Here we present multiple coral‐based sea surface temperature reconstructions from Yongle Atoll, in the South China Sea over the last ~1,250 years (762–2013 Common Era [CE]). Reconstructed coral Sr/Ca‐sea surface temperatures indicate that the “Little Ice Age (1711–1817 CE)” period was ~0.7°C cooler than the “Medieval Climate Anomaly (913‐1132 CE)” and that late 20th century warming of the western Pacific is likely unprecedented over the past millennium. Our findings suggest that the Western Pacific Warm Pool may have expanded (contracted) during the Medieval Climate Anomaly (Little Ice Age), leading to a strengthening (weakening) of the Asian summer monsoon, as recorded in Chinese stalagmites.